Retrospective analysis of trauma patients transported by dispatch monitored type B ambulances to Dhulikhel Hospital, Kavre, Nepal, 2019–2023 - Maxwell L. Mantych; Shiva Neupane; Machchendra Sapkota; Laura D. Cassidy; Sarah C. Young; Ronald Anguzu; Samjhana Basnet (International Journal of Emergency Medicine)
Abstract Background Timely emergency medical services (EMS) are particularly important among trauma patients, as inefficient EMS systems can result in potentially avoidable death before reaching a hospital. The Dhulikhel Hospital Dispatch Center coordinates and monitors a growing network of ambulances, including seven Type B ambulances staffed with a trained prehospital care provider and medical equipment. This study evaluates the prehospital care and outcomes of trauma patients transported by Type B ambulances to Dhulikhel Hospital’s Emergency Department, as monitored by the Dispatch Center. Methods Data were collected via a retrospective chart review of Dispatch Center records, including patient demographics, injury mechanisms, prehospital care, and outcomes. Patients were included if they experienced physical trauma and were transported by a Type B ambulance to Dhulikhel Hospital’s Emergency Department between 2019 and 2023. Results Between 2019 and 2023, 224 trauma patients were transported to the hospital and received prehospital care services from Type B ambulances monitored by the Dispatch Center. Most patients were male (59%), and nearly half were aged 18–44 (49%). The median total transport time for Dhulikhel Hospital-owned Type B ambulances was 40 min. Type B ambulances reached patients across 24 municipalities (88% in Kavrepalanchowk and Sindupalchowk districts). Falls (55%) and road traffic accidents (30%) were the most common injury mechanisms, followed by physical assault (7%). Falls were significantly associated with female, pediatric, and geriatric patients (p < 0.05), while road traffic accidents predominated among males, particularly in adults aged 25–34 years (p < 0.05). Approximately one-third of patients admitted to the hospital after evaluation in the emergency department experienced multiple injuries, and the most prevalent diagnosis of admitted cases were extremity fractures (52%). Conclusion Trauma cases accounted for 15% (227/1541) of all patients who received transport and prehospital care services from a Type B ambulance monitored by the Dispatch Center between 2019 and 2023. This study demonstrates the critical role of Type B ambulances and an integrated dispatch center in advancing timely and efficient prehospital care for trauma patients in Nepal.